The Accuracy of Estimating Fetal Weight using Ultrasound in Women with High Body Mass Index - Kilani, Rami; Al Eyadeh, Wesam; Qasrawi, Hussam; Abu Atileh, Luay (Jordan Medical Journal, 2019)
Objective: To determine the effect of maternal obesity on estimated fetal weight.Design: Prospective cohort study. Setting: Tertiary care hospital in Amman Al-Bashir Hospital. Subjects: 326 women admitted for elective delivery between November 2015 and January 2016Intervention: Participants were divided into their weight parameters: normal, overweight, obese, and extremely obese according to WHO obesity standards. A pre-delivery ultrasound exam was performed, and estimated fetal weight was calculated. Actual fetal weight was measured 30 minutes after delivery. The difference between actual and estimated fetal body weight was calculated. Main outcome measures: Estimated fetal weight and measured postpartum fetal weight are equal. Results: There was a significant difference between the estimated fetal weight and the actual fetal weight. This difference was measured to be higher in extremely obese mothers when compared to mothers with a lower BMI. The difference between estimated fetal weight and actual fetal weight was 222 grams for the normal weight population, 240 grams for the overweight population, 287 grams for the obese population and 466 grams for the extremely obese population (P < 0.01). Conclusion: Fetal weight assessment becomes increasingly less accurate with increasing maternal BMI. Obstetricians need to take this into consideration when managing obese patients with complications.